Some classes of statistically convergent sequences of fuzzy numbers generated by a modulus function - Çakan, Ü.; Altin, Y. (University of Sistan and Baluchestan, 2015)
The purpose of this paper is to generalize the concepts of statistical convergence of sequences of fuzzy numbers defined by a modulus function using difierence operator ? and give some inclusion relations. © 2015, University of Sistan and Baluchestan. All rights reserved.
Keywords: Modulus function; Sequence of fuzzy numbers; Statistical convergence